Camoufl-Ages: Body Assemblages at the Time of the Apocalypse - Botta, Giuseppina (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2013)
Performance deals with embodiment, presence, agency and event. It is related to representation and consists in the display of an action with the presence of observers (Schechner). In Margaret Atwood’s Oryx and Crake (2003) and The Year of the Flood (2009) performance is connected with the protagonists’ struggle for survival, which proves particularly complex because of the complete subversion of the environmental conditions, in a post-apocalyptic future dominated by the harsh consequences of an unscrupulous exploitation of genetic engineering. Scholars have discussed the theme of survival in Atwood’s novels with regard to power politics and victimhood. In my essay through a series of ecocritical studies (Warren, Otto, Castricano, Sehadri), I will explore the distorted relationship between human culture and environment provoked by the excessive manipulation of the living matter, whether human or animal, which alters the perception of the self and of being in general. My focus will be on the notions of mimicry and camouflage.